Penerapan Modul Ajar Literasi Inovatif Berbantuan Teks Narasi Imajinatif untuk Peningkatan Kemampuan Membaca Pemahaman Siswa Kelas 2 SD - Milati Azka; Panca Dewi Purwati (Journal on Education, 2025)
This research aims to improve students' reading comprehension skills in material on maintaining personal health in the Indonesian language subject for grade 2 students at SDN Wates 01 through the application of innovative literacy teaching modules assisted by imaginative narrative texts. This research uses a mix method which combines quantitative and qualitative approaches. The research results showed a significant increase in the average student score from 65 (42% completeness with quite effective criteria) on the pretest to 85 (85% completeness with very effective criteria) on the posttest. Innovative literacy teaching modules assisted by imaginative narrative texts have been proven to improve students' reading skills and understanding of material on maintaining personal health, especially dental health, Indonesian language subjects.